A modified Cued Recall Test for detecting prodromal AD in adults with Down syndrome. Issue 1 (3rd October 2022) - Krinsky‐McHale, Sharon J.; Hartley, Sigan; Hom, Christy; Pulsifer, Margaret; Clare, Isabel C.H.; Handen, Benjamin L.; Lott, Ira T.; Schupf, Nicole; Silverman, Wayne; ,
Abstract: Introduction: The development of valid methods to diagnose prodromal Alzheimer's disease (AD) in adults with Down syndrome (DS) is one of the many goals of the Alzheimer's Biomarkers Consortium—Down Syndrome (ABC‐DS). Methods: The diagnostic utility of a modified Cued Recall Test (mCRT) was evaluated in 332 adults with DS ranging from 25 to 81 years of age. Total recall was selected a priori, as the primary indicator of performance. Multiple regression and receiver‐operating characteristic (ROC) analyses were used to compare diagnostic groups. Results: Performance on the mCRT, as indicated by the total recall score, was highly sensitive to differences between diagnostic groups. ROC areas under the curve (AUCs) ranging from 0.843 to 0.955, were observed., Discussion: The mCRT has strong empirical support for its use in clinical settings, as a valuable tool in studies targeting biomarkers of AD, and as a potential outcome measure in clinical trials targeting AD in this high‐risk population.